Analysis of Six-Phase Interior Permanent Magnet Synchronous Machines for Optimal Parameter Considerations - Tanmoy Dey; Amit Kumar Chowdhury; Sk Mehboob Alam; Surajit Mondal (International Journal of Applied Power Engineering (IJAPE), 2018)
Understanding the merits of six-phase interior permanent magnet synchronous machines (IP-MSMs) over their three-phase counterparts, this paper analyses the six-phase machine for optimal parameter and performance considerations. Initially, a mathematical model of the six-phase IPMSM is developed employing the dq-axis theory and performance predicted by the model is verified under identical operating conditions with those using a machine designed and tested through finite element analysis (FEA). The developed and verified machine model is then employed to exclusively derive the relation between various machine parameters in order to obtain optimum flux weakening region in the six-phase IPMSM. Thereafter, the equations derived on the basis of maximum torque per ampere (MTPA) control theory are analyzed to understand the effect of various parameters and variables in influencing the machine’s performance in the ‘constant torque’ region and ‘constant power’ region, power output capability, a ratio of reluctance torque to magnet-assisted torque with changes in the stator current vector etc. This is the contribution of this paper.